GREEN BIOSYNTHESIZED SILVER NANOPARTICLES MEDIATED BY TRICHOSANTHES CUCUMERINA EXTRACT AND ITS BIOLOGICAL ACTIVITIES - Bello, Oluwasesan M.; Shema, Abdulsalam Shehu; Saulawa, Aisha Ibrahim (FUDMA JOURNAL OF SCIENCES, 2021)
Biosynthesized Nanoparticles especially from plants are a new research trend nowadays. In this study, green biosynthesis of silver nanoparticles (TCAgNPs) employing Trichosanthes cucumerina methanol leaf extract was realized. The antioxidant and anti-inflammatory activities of both the methanol extract of T. cucumerina and TCAgNPs were carried out and compared. Indomethacin and ascorbic acid were employed as a positive control for these activities respectively.  Fourier transform infrared spectroscopy (FT-IR) scanning electron microscopy (SEM) and Ultraviolet-visible spectroscopy were employed to characterize the formation of TCAgNPs. The TCAgNPs showed absorption bands at around 340-440 nm which is a distinctive band for Ag Nanoparticles and functional groups accountable for Ag nanoparticles synthesized by plants were noticed in the FTIR. TCAgNPs were spherical in morphology as seen from the SEM images.  TCAgNPs displayed better antioxidant and anti-inflammatory activities at 400 ug/ml (9.79Â±0.58) as compared with its polar extracts (7.74Â±0.58) but both the polar part (52.06Â±1.27) and TCAgNPs (61.72Â±2.54) were better in anti-inflammatory activity when compared with the positive control indomethacin (antiinflammatory) (48.30Â±0.23). This study revealed that AgNPs from plants can find germaneness in food, drugs, environmental sciences and drugs.
Keywords: antioxidant; nanoparticles; T. cucumerina; FTIR; green biosynthesized; anti-inflammatory activities